A Strategy for Screening Monoclonal Antibodies for Arabidopsis Flowers - Shi, Qian; Zhou, Lian; Wang, Yingxiang; Ma, Hong (Frontiers in Plant Science, 2017)
The flower is one of the most complex structures of angiosperms and is essential for sexual reproduction. Current studies using molecular genetic tools have made great advances in understanding flower development. Due to the lack of available antibodies, studies investigating the localization of proteins required for flower development have been restricted to use commercial antibodies against known antigens such as GFP, YFP and FLAG. Thus, knowledge about cellular structures in the floral organs is limited due to the scarcity of antibodies that can label cellular components. To generate monoclonal antibodies that can facilitate molecular studies of the flower, we constructed a library of monoclonal antibodies against antigenic proteins from Arabidopsis inflorescences and identified 61 monoclonal antibodies. 24 of these monoclonal antibodies displayed a unique band in a Western blot assay in at least one of the examined tissues. Distinct cellular distribution patterns of epitopes were detected by these 24 antibodies by immunofluorescence microscopy in a flower section. Subsequently, a combination of immunoprecipitation and mass spectrometry analysis identified potential targets for three of these antibodies. These results provide evidence for the generation of an antibody library using the total plant proteins as antigens. Using this method, the present study identified 61 monoclonal antibodies and 24 of them were efficiently detecting epitopes in both Western blot experiments and immunofluorescence microscopy. These antibodies can be applied as informative cellular markers to study the biological mechanisms underlying floral development in plants.